A Service Quality, Price Perception, and Therapeutic Communication in Sarangan Medicare Clinic Malang - Tambunan, Damelia Basauli; Panjarwanto, Dwi Andhika (Universitas Ciputra Surabaya, 2024)
In the rapidly evolving landscape of healthcare, patient retention remains a critical concern for clinics worldwide. Sarangan Medicare Clinic in Malang seeks to understand the key determinants influencing patients' decisions to revisit. However, a research gap exists in the precise understanding of how Service Quality, Price Perception, Therapeutic Communication, and Trust interplay in shaping these intentions. To fill this gap, this study utilizes Structural Equation Modelling Partial Least Square (SEM-PLS), chosen for its capacity to parse intricate relationships between multiple variables efficiently. The findings reveal significant associations between the quality of service, the perception of price fairness, effective therapeutic communication, and the establishment of trust, all converging to shape a patient's intent to return. These insights are not only pivotal for Sarangan Medicare Clinic in Malang but also hold broader implications for similar healthcare institutions striving for patient retention and satisfaction.